Machine learning and high spatial resolution multi-temporal Sentinel-2 imagery for crop type classification - Maponya, Mmamokoma Grace (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPhil)--Stellenbosch University, 2019.